Silencing of Long Non-Coding RNA LINC00607 Prevents Tumor Proliferation of Osteosarcoma by Acting as a Sponge of miR-607 to Downregulate E2F6 - Zheng, Yuehuan; Chen, Zhe; Zhou, Zezhu; Xu, Xiangyang; Yang, Huilin (Frontiers in Oncology, 2021)
Osteosarcoma is a common malignant bone tumor prone to children and adolescents. Although lots of studies reveal that long non-coding RNAs (lncRNAs) are vital regulators of osteosarcoma (OS). whether any other long non-coding RNAs participate in osteosarcoma’s progression remains unclear. In the present study, we identified a long noncoding RNA LINC00607, which facilitate OS proliferation, migration and invasion. Depending on RNA-sequencing results, LINC00607 is significantly upregulated in pulmonary metastasis within OS. Functional experiments indicated that LINC00607 promotes migration and invasion of endothelial cells to exacerbate epithelial-mesenchymal transition (EMT). Further, we verified that LINC00607 tethering miR-607 promotes OS invasion by RNA pull-down assay and invasion assay. Bioinformatic prediction and rescue experiment demonstrated that E2F6, a transcriptional factor, functions downstream of LINC00607/miR-607. Finally, LINC00607 promotes OS tumor growth in vivo. Our work presented here revealed that LINC00607 works as a sponge of miR-607 to upregulate E2F6, which promote tumor proliferation in osteosarcoma. These findings provide novel potential therapeutic targets for osteosarcoma treatment.